2015
DOI: 10.1002/2015jd023493
|View full text |Cite
|
Sign up to set email alerts
|

Estimate of carbonyl sulfide tropical oceanic surface fluxes using Aura Tropospheric Emission Spectrometer observations

Abstract: Quantifying the carbonyl sulfide (OCS) land/ocean fluxes contributes to the understanding of both the sulfur and carbon cycles. The primary sources and sinks of OCS are very likely in a steady state because there is no significant observed trend or interannual variability in atmospheric OCS measurements. However, the magnitude and spatial distribution of the dominant ocean source are highly uncertain due to the lack of observations. In particular, estimates of the oceanic fluxes range from approximately 280 Gg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
105
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 66 publications
(129 citation statements)
references
References 26 publications
12
105
3
Order By: Relevance
“…Satellite data have shown that tropospheric OCS is elevated above the North Indian and northwest tropical Pacific oceans, and inverse models using enhanced oceanic emissions reproduced a similar pattern (Kuai et al, 2015). Global oceanic emissions would need to amount to 800-1000 Gg S yr -1 to fully account for this missing source.…”
Section: Oceanmentioning
confidence: 99%
See 2 more Smart Citations
“…Satellite data have shown that tropospheric OCS is elevated above the North Indian and northwest tropical Pacific oceans, and inverse models using enhanced oceanic emissions reproduced a similar pattern (Kuai et al, 2015). Global oceanic emissions would need to amount to 800-1000 Gg S yr -1 to fully account for this missing source.…”
Section: Oceanmentioning
confidence: 99%
“…A missing source of about 600-800 Gg S yr -1 in the atmospheric budget of OCS has recently been 15 identified by several top-down approaches (Berry et al, 2013;Glatthor et al, 2015;Kuai et al, 2015;Wang et al, 2016). Satellite data have shown that tropospheric OCS is elevated above the North Indian and northwest tropical Pacific oceans, and inverse models using enhanced oceanic emissions reproduced a similar pattern (Kuai et al, 2015).…”
Section: Oceanmentioning
confidence: 99%
See 1 more Smart Citation
“…A monthly mean of TES OCS results from June 2006 was published in Kuai et al (2015), which further validated the concept that direct ocean emissions of OCS are much greater than previously thought (Berry et al, 2013). The published data included retrievals over the ocean around ±40…”
Section: Previous Estimates From Satellitementioning
confidence: 58%
“…These groundbased in situ measurements are only at limited sites and aircraft measurements cover relatively short time periods. The emerging of the remote sensing data, including ground-based (Notholt et al, 2003) and satellite (Barkley et al, 2008;Kuai et al, 2014Kuai et al, , 2015Glatthor et al, 2015) measurements, will potentially increase the number of OCS measurements largely. The satellite data provide a wide distribution of OCS; however, they are mainly sensitive in the upper troposphere and stratosphere (Barkley et al, 2008;Glatthor et al, 2015) or mid-troposphere (Kuai et al, 2014), and therefore have little help in constraining the land fluxes.…”
Section: Introductionmentioning
confidence: 99%